2015
DOI: 10.5301/tj.5000233
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life and Cosmesis after Breast Cancer: Whole Breast Radiotherapy vs Partial Breast High-dose-rate Brachytherapy

Abstract: Even at longer follow-up, quality of life is similar after partial or whole breast irradiation. Cosmesis is better after partial breast irradiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…Twenty‐five studies were included in the systematic review, 1 article studied the prevalence rate of FoR after RT in mainland China, 2 longitudinal studies measured patient's FoR level over/after RT, and the remaining 22 studies evaluated the impact of RT on patient's FoR. Conflicting evidence was found among these 22 studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Twenty‐five studies were included in the systematic review, 1 article studied the prevalence rate of FoR after RT in mainland China, 2 longitudinal studies measured patient's FoR level over/after RT, and the remaining 22 studies evaluated the impact of RT on patient's FoR. Conflicting evidence was found among these 22 studies.…”
Section: Resultsmentioning
confidence: 99%
“…All of them were evaluated using the QualSyst criteria, and none of them had the score of limited quality (see Table 1). However, 10 studies were excluded from further meta-analysis (1 prevalence rate study, 34 2 longitudinal studies, 35,36 and 1 strong outlier in funnel plot, 37 and 6 did not report specific statistic values 16,22,24,[38][39][40] ). Therefore, 15 articles were finally included in the meta-analysis.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…The use of interventional radiotherapy (BT) has increased in the last decades, most probably due to technical improvements, allowing to deliver higher doses to the target while reducing dose and volume of organs at risk [9]. Moreover, BT in Italy has been increasingly based on a multidisciplinary approach, with a growing number of high-quality publications of excellent treatment results [9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31]. These innovations, in the context of a rapid diffusion of 3D planning, with an increased use of computed tomography (CT), magnetic resonance imaging (MRI), positron emission tomography (PET)/CT, and ultrasound, favored the diffusion of image-guided brachytherapy (IGBT) [32] with related clinical benefits.…”
Section: Discussionmentioning
confidence: 99%
“…In China, more than 169 000 females are diagnosed with breast cancer every year, and approximately 45 000 females will die from it [ 2 ]. It has been reported that the diagnosis and treatment of breast cancer put great pressure on patients during their breast cancer journeys, especially emotional changes, such as anxiety, depression, and fear [ 3 , 4 ]. These changes seriously affect the patients’ quality of life.…”
Section: Introductionmentioning
confidence: 99%